Industrial energy consumption analysis - Ikhsan, Azman; Abdul Rahman, Mohd. Norani; Abdullah, Hayati (Jawatankuasa Penyeldikan & Perundingan, Fakulti Kej. Kimia & Kej. Sumber Asli, UTM, 1993)
An industrial energy analysis was conducted to identify the local energy pattern for every industrial sector and the improvement that can be undertaken on energy consumption by the industry in Malaysia. A Questionnaire was distributed to the FMM members. Energy management awareness among the respondent were fairly high where the majority of the large scale companies have their own Energy Management Team (EMT) and the majority of the SMI do not have their EMT. Most companies have introduced energy saving measures in their operations of which most of the current and future activities are in the area of thermal system, energy auditing, instrumentation and building envelope. Lack of relevant information on energy technology was the main obstacle to the implementation of energy conservation program in these companies. Other problems identified according to priority were costing, technology, manpower, government measures and supply of energy. The energy consumed by the industries are derived from diesel, heavy and light fuel oil. LPG, electricity and others (including coal, rubber wood chips, petrol, etc). The overall energy consumptions composed of 12% diesel, 33% light fuel oil, 7% heavy fuel oil, 2% LPG, 0.01% electricity and 46% of other energy sources. Energy audit, conducted on 10 factories of various sectors, identified the potential energy conservation measures. These measures were recommended to the management of the individual factory or their technical staff for economic feasibility studies. Finally, recommendation were made for the government to play an important role in guiding, informing and monitoring the energy usage through relevant policies and the setting up of a center for energy studies.